2011
DOI: 10.1007/s10493-011-9454-4
|View full text |Cite
|
Sign up to set email alerts
|

Do plant mites commonly prefer the underside of leaves?

Abstract: The adaxial (upper) and abaxial (lower) surfaces of a plant leaf provide heterogeneous habitats for small arthropods with different environmental conditions, such as light, humidity, and surface morphology. As for plant mites, some agricultural pest species and their natural enemies have been observed to favor the abaxial leaf surface, which is considered an adaptation to avoid rain or solar ultraviolet radiation. However, whether such a preference for the leaf underside is a common behavioral trait in mites o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 32 publications
0
34
0
Order By: Relevance
“…Sakai and Osakabe (2010) found that the distribution of T. urticae females was different between upper and lower leaf surfaces as a result of UV-avoidance behavior. The deleterious effects of solar UVR may be significant factors restricting plant-dwelling mites, including predacious mites, to the lower leaf surfaces or inside domatia (Ohtsuka and Osakabe 2009;Onzo et al 2010;Sudo and Osakabe 2011). These species might occupy habitat in which they encounter predators or competitors less frequently or gain nutritional advantage through increased fecundity on the upper leaf surfaces versus the lower leaf surfaces.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sakai and Osakabe (2010) found that the distribution of T. urticae females was different between upper and lower leaf surfaces as a result of UV-avoidance behavior. The deleterious effects of solar UVR may be significant factors restricting plant-dwelling mites, including predacious mites, to the lower leaf surfaces or inside domatia (Ohtsuka and Osakabe 2009;Onzo et al 2010;Sudo and Osakabe 2011). These species might occupy habitat in which they encounter predators or competitors less frequently or gain nutritional advantage through increased fecundity on the upper leaf surfaces versus the lower leaf surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…These species might occupy habitat in which they encounter predators or competitors less frequently or gain nutritional advantage through increased fecundity on the upper leaf surfaces versus the lower leaf surfaces. In fact, a part of herbivorous mites exploit not only the lower but also the upper leaf surfaces of host plants (Foott 1963;Jones and Parrella 1984;Sudo and Osakabe 2011). Of those species, the European red mite Panonychus ulmi (Koch) (Acari: Tetranychidae), moves from the lower to the upper leaf surfaces as a response to increasing density of a superior competitor T. urticae on the lower leaf surfaces (Osakabe et al 2006).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, most plant-dwelling arthropods, including many species of stink bugs, tend to lay their eggs on the undersides of plant leaves [17][18][19][20]. Laying eggs on the undersides of leaves is generally considered to provide a sheltered microclimate for developing embryos, offering protection against wind, rain, overheating, and desiccation.…”
Section: Egg Pigmentation Protects Developing Embryos Against Ultravimentioning
confidence: 99%
“…Many plant-dwelling mites preferentially inhabit lower rather than upper leaf surfaces of their host plants (Sudo and Osakabe 2011). Solar ultraviolet-B (UVB; 280 Ð315 nm wavelengths) radiation may be a major factor affecting the within-leaf (upper/lower) distribution of mites (Ohtsuka and Osakabe 2009, Suzuki et al 2009, Sakai and Osakabe 2010.…”
mentioning
confidence: 99%